2020
DOI: 10.4049/jimmunol.1900053
|View full text |Cite
|
Sign up to set email alerts
|

Roquin-1 Regulates Macrophage Immune Response and Participates in Hepatic Ischemia–Reperfusion Injury

Abstract: With the development of liver surgery, ischemia-reperfusion (IR) injury has received increasing attention. Roquin-1 has been shown to play an important role in innate immune and immune balance. We demonstrate that Roquin-1 expression increased at 1 h after IR and then decreased in C57B/L mice. The immunofluorescence double-label showed that Roquin-1 was mainly expressed in macrophages (mø). Furthermore, we used clodronate liposomes to remove mø, and injected the bone marrowderived mø (BMDM) through the tail ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…AMPK is an energy-sensing serine/threonine protein kinase that maintains cellular metabolic homeostasis [8]. Recent reports suggest that AMPK activation (phosphorylation of α subunit at thr172) and/or downstream mTOR inhibition are involved in inflammation alleviation and macrophage and/ or microglial polarization to the M2-phenotype [56][57][58]. The present study showed, for the first time, that Ac2-26 increased AMPKα phosphorylation and decreased mTOR phosphorylation in the setting of cerebral I/R, these effects were again abrogated by WRW4.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is an energy-sensing serine/threonine protein kinase that maintains cellular metabolic homeostasis [8]. Recent reports suggest that AMPK activation (phosphorylation of α subunit at thr172) and/or downstream mTOR inhibition are involved in inflammation alleviation and macrophage and/ or microglial polarization to the M2-phenotype [56][57][58]. The present study showed, for the first time, that Ac2-26 increased AMPKα phosphorylation and decreased mTOR phosphorylation in the setting of cerebral I/R, these effects were again abrogated by WRW4.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, therapeutics should normalize both male and female differences as cetirizine in allergic inflammation [84]. F4/80+ macrophages, also participate in tissue injury after hepatic, myocardial, cerebral, and intestinal I/R [79][80][81][82][83]. In addition, intestines from male mice express higher levels of F4/80+ macrophages after I/R compared to intestines from female mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study showed that MyD88-dependent activation of IL-1α in KCs promoted sterile inflammation in APAP-induced acute hepatic injury (54). Another study demonstrated that roquin-1 affected the polarization of KCs through regulating AMPKα activity following hepatic IR injury (55). Meanwhile, it has been reported that lycopene attenuated obesity-induced inflammation and insulin resistance via regulating macrophage polarization (56).…”
Section: Discussionmentioning
confidence: 99%